2019
DOI: 10.1039/c9gc01333d
|View full text |Cite
|
Sign up to set email alerts
|

Direct one-step synthesis of a formally fully bio-based polymer from cellulose and cinnamon flavor

Abstract: Direct fully bio-based polymer synthesis by cellulose modification involving simply mixing cellulose and cinnamaldehyde “cinnamon flavor” in an ionic liquid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 43 publications
3
27
0
Order By: Relevance
“…Our previous report confirmed that the oxidative esterification does not proceed when dimethyl sulfoxide (DMSO) is used as the solvent without IL. To investigate the influence of the IL on the reaction result, we tested ILs containing various anions (Table ).…”
Section: Results and Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Our previous report confirmed that the oxidative esterification does not proceed when dimethyl sulfoxide (DMSO) is used as the solvent without IL. To investigate the influence of the IL on the reaction result, we tested ILs containing various anions (Table ).…”
Section: Results and Discussionsupporting
confidence: 73%
“… a Reaction conditions: [ROH]/[ 1 ]/[IL]/[DMSO] = 1/1/1/20 (molar ratio), 24 h, 60 °C, Ar atmosphere. b On the basis of the IR absorption band at ∼1730 cm –1 corresponding to CO stretching (Figure ). c Data in previous report (ref ). d DS side value derived from the acetate anion. …”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations